2018
DOI: 10.5582/bst.2018.01103
|View full text |Cite
|
Sign up to set email alerts
|

An ethanolic extract of the aerial part of <i>Siegesbeckia orientalis </i>L. inhibits the production of inflammatory mediators regulated by AP-1, NF-κB and IRF3 in LPS-stimulated RAW 264.7 cells

Abstract: Herba Siegesbeckiae (HS, the dried aerial part of Siegesbeckia orientalis L.) is a commonly used traditional Chinese medicinal herb for treating inflammatory diseases. HS has been reported to exert anti-inflammatory effects by inhibiting the MAPKs and NF-κB pathways, the downstream effectors of TLR4 signalling. This study aims to further investigate the involvement of TLR4 signalling cascades in the effects of an ethanolic extract of HS (HS for short) on inflammatory mediators in murine macrophages. HS was ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
5
0
1
Order By: Relevance
“…Once the stimulus is resolved, the process returns to the latent state. Many studies had proved that the NF-κB signaling pathway is involved in the occurrence and development of inflammation-related diseases and cancer [33,34]. To investigate the interrelation between NF-κB signaling pathway and RE, we furthermore performed western blotting assay on the esophageal tissue proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Once the stimulus is resolved, the process returns to the latent state. Many studies had proved that the NF-κB signaling pathway is involved in the occurrence and development of inflammation-related diseases and cancer [33,34]. To investigate the interrelation between NF-κB signaling pathway and RE, we furthermore performed western blotting assay on the esophageal tissue proteins.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 can be activated by LPS, it may be the target protein of Chinese herbs, which inhibited LPS-induced in ammation in RAW264.7 cells [41]. Research about Chinese herbs found that Chinese herbs inhibited LPS-induced TLR4 and MyD88 expressions in RAW264.7 macrophages, as a result, inhibiting the production of in ammatory mediators [42,43]. Of the several transcriptional factors activated by in ammatory responses during bacterial infections, NF-κB plays a critical role in several signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lower NO levels were detected after the GSYJ treatment than after the LPS treatment ( Figure 6(c)). [18]. GSYJ inhibits the expression of the IL-1β, IL-6, RANTES, and iNOS mRNAs in LPS-induced macrophages.…”
Section: Effects Of Gsyj On Lps-induced Changes In the Mrna And Protementioning
confidence: 98%